LOCAL OWN-SOURCE REVENUE AND ITS DETERMINANTS - William, Fandy; Harjanto, Karina (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The purpose of this research is to obtain empirical evidence about the effect of Total Population, Domestic Investment, and Gross Regional Domestic Product towards Local Own-source Revenue. The object of this research are districts and cities in the province of Banten in 2016-2020. Sample of this research were selected using census method and testing was performed using multiple linear regression method. The observation of this research are 8 Districts and cities in the province of Banten namely Pandeglang District, Lebak District, Tangerang District, Serang District, Tangerang City, Cilegon City, Serang City, and South Tangerang City. The result of this research are Total Population, Domestic Investment, and Gross Regional Domestic Product simultaneously have significant effect toward Local Own-source Revenue. Partially, Total Population and Gross Regional Domestic Product has a significant effect towards Local Own-source Revenue, while Domestic Investment does not have a positive effect toward Local Own-source Revenue.